A Tropical Plant with Friends in Cold Places: The Formation of the UK Rice Research Community. (May 2020) - Sadanandom, Ari; Murchie, Erik H.
Abstract : The trend for translating fundamental plant science to applied solutions in agriculture has accelerated the formation of global networks and partnerships to achieve common global goals in food security. Here we highlight a thriving rice research community in the UK contributing to long-term approaches to understand rice biology.